2005
DOI: 10.1007/s10710-005-7620-3
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Collective Behavior in Evolving Populations of Flying Agents

Abstract: Abstract. We demonstrate the emergence of collective behavior in two evolutionary computation systems, one an evolutionary extension of a classic (highly constrained) flocking algorithm and the other a relatively un-constrained system in which the behavior of agents is governed by evolved computer programs. We describe the systems in detail, document the emergence of collective behavior, and argue that these systems present new opportunities for the study of group dynamics in an evolutionary context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…This process was repeated regardless of whether the predator successfully captured the prey. The simplicity of the predator algorithm and relative simplicity of the prey algorithms supports the findings of earlier digital swarm studies that complex swarm behaviors can be described by simple rules applied over a group of locally-interacting agents [48,49].…”
Section: Evolved Predator and Prey Behaviorsupporting
confidence: 74%
“…This process was repeated regardless of whether the predator successfully captured the prey. The simplicity of the predator algorithm and relative simplicity of the prey algorithms supports the findings of earlier digital swarm studies that complex swarm behaviors can be described by simple rules applied over a group of locally-interacting agents [48,49].…”
Section: Evolved Predator and Prey Behaviorsupporting
confidence: 74%
“…That said, there are many other potential causes of swarming behavior that we do not address in this study. For example, some studies have investigated the evolution of predator behavior in response to prey density [56], the role of relative predator and prey speeds on the evolution of grouping behavior [66], elaborated upon the interaction between ecology and the evolution of grouping behavior [55,64], and explored the role of group vigilance (i.e., the "many eyes" hypothesis) in the evolution of grouping behavior [16,43]. Two recent studies have explored the coevolution of predator and prey behavior in the presence of the predator confusion effect [40,32], and found that the predator confusion effect is sufficient to select for the evolution of swarming behavior in the absence of any other group benefits.…”
Section: Related Workmentioning
confidence: 99%
“…For the second stage, we use a modified bird flocking algorithm [30,31]. Each growth cone is subject to a number of weighted 'urges', including 1. a destination urge (w d u u u d ), which is directed up the attractant gradient 2. an avoidance urge (w a u u u a ) to avoid already generated bundles 3. a velocity urge (w v u u u v ) to match the average velocity of nearby agents 4. a spacing urge (w s u u u s ) to avoid collisions with nearby agents 5. a center urge (w c u u u c ) to steer toward the centroid of nearby agents and keep the group cohesive Figure 1.1 Simulation of nerve fiber growth by single agents.…”
Section: Modified Flocking Algorithmmentioning
confidence: 99%